PEMANFAATAN SITUS SEJARAH MAKAM MAHLIGAI SEBAGAI SUMBER BELAJAR IPS - Eti Damayanti Simamora; Sakti Ritonga (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2025)
This study aims to analyze the potential and utilizationof the historical site of the Mahligai Tomb in Barus as a learningresource in Social Sciences (IPS) learning. The Mahligai Tomb is one of the important sites in the history of the entry of Islam into the archipelago which has high educational value. This study uses a qualitative approach with data collection techniques through interviews with IPS teachers, traditional figures, local historians, students, and local residents. The results of the study indicate that the Mahligai Tomb site has historical, cultural, and religious values that can enrich students' understanding of Islamic history and local culture.In addition, its utilization In IPS learning has been proven to increase students' interest in learning, strengthen cultural identity, and build awareness of preserving historical heritage. However, the utilization of this site still faces several challenges, such as the lack of integration in the curriculum and limited support for educational facilities. This study recommends the development of a more systematic and collaborative historical site-based learning strategy between schools, communities, and the government.